An Ethnographic Study in Tamang Community: Socio-Cultural Process (Pashupati Pragya पशुपति प्रज्ञा, 2025)
This article explores the knowledge construction transformation process in Tamang culture with a methodological viewpoint. This study was conducted in Tamang village named Duble, Okhaldhunga. Being an ethnographic researcher, I collected data through participant observation, informal and in-depth interview. The main focusing areas were daily life of the respondents and their main occupation regarding knowledge. There were three research questions; how do Tamang people construct knowledge in relation to survive? How do they transfer their knowledge in their culture from one generation to another generation? What changes they are feeling on knowledge construction and transformation process? I have completed this study is based on ethnography under the supervision of school of education. Five Tamang respondents were selected by using purposive sampling method.Researcher has focused and employed interpretive paradigm in order to explore the knowledge construction and transferring process in Tamang people. Researcher has used interpretative ideas, views and their voices in a natural and simple metaphoric way. Tamang people were very laborious, honest simple as well as dedicated in their nature. They were generating and transferring knowledge from form their culture. Social constructivism was the process of knowledge construction model. They have constructed knowledge by seeing, doing self and experience in the family and community. They were transferring their knowledge through their elder members of the family and the duty formation by the community. Informal network of knowledge, oral history, object, needs of the community were playing role to construct and transform knowledge. Some knowledge was based on the need assessment like Bonbo and Lama which were very necessity for them than they feel great job to that. They were performing their job in a simple way but that was very hard and difficult for us to define it. They were feeling change in their daily life and it has changed them in the process of knowledge construction and transformation process regarding hybridization in agriculture and schooling. Tamang culture was favourable to construct and transfer of knowledge.